Między jasnością a ciemnością. O wybranych leksemach wyrażających intensywność światła w twórczości Janusza Stanisława Pasierba - Kaptur, Ewa; Sławek, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The poetic texts of priest Pasierb present a peculiar sensitivity to the names of colours. The author of Koziorożec ( Capricorn ) paid particular attention to the role of light, hence his works present a separate category of expressions regarding light and darkness, flash and brightness. It is the result of, among others, the culturallyconditioned evaluation of light and dark and the related axiological attitude towards the world. Also present are numerous lexemes situated in the lexical field of, for instance, red, yellow, golden, blue, black and white. The collected material shows that the names of colours present in Pasierb’s works do not so much name reality as co-create the mood of particular texts, creating as a result a set of delicate poetic impressions.